Avaliação da eficiência energética de uma bomba hidráulica uti-lizada em uma plataforma de descarga de grãos - Figueiredo, João Luiz Fontana de (2018)
The population advances quickly in the regard to the increase in consumption energy in many forms. Brazil, considered the "breadbasket of the world", has innumerable grain storage units in his territory, and these, consume a lot of energy in their reception, drying and storage processes. Particularly in the process of receiving grains, there is a large energy consumption in the discharged platforms responsible for receiving the products in bulk. These discharged platforms are operated by hydraulic pumps driven by an electric motor, which operates uninterruptedly throughout the basculation pro-cess. The present work aims to perform a study of energy efficiency in the basculation system of the discharged platform, from the use of electric devices to control the oper-ation of the engine. For this purpose, two scenarios were established. The first sce-nario considers the platform in its current state, with engine starting made by a star-triangle key. In the second scenario, star-delta start is switched off, and a frequency inverter and a programmable logic controller (PLC) are coupled to control the electric motor. For the two scenarios, the active and reactive energy consumptions were meas-ured in the discharged platform using an energy analyzer, and the costs of the energy consumed in the period of one year were calculated. Finally, the discounted Payback was calculated to evaluate the economic feasibility of installing the proposed equip-ment. The results obtained were as follows: For the current scenario, the energy used to raise a ton was 35.44.10-3 kWh/ton, for the proposed scenario, with a frequency inverter, this index was 32.78.10-3 kWh/ton. With an annual projection, the current sce-nario would consume the equivalent of 10,921.35 kWh and the proposed scenario 10,100.81 kW, generating an annual savings with equipment installation of R$721.49, and the discounted Payback found of approximately 31 years. It can be concluded, therefore, that there is a reduction of electric energy consumption from the use of the frequency inverter, but the time of return of the invested capital is very long, making the proposal economically unfeasible.